Uporabnost metod GIS pri načrtovanju knjižničnih storitev - Vidiček, Matija (Knjižnica, 2010)
In information era, Geographical Information Systems (GIS) are more and more accessible for general application and consequently gaining in importance. GIS information system enables storing and analyzing data, but it differs from other information systems as the data are linked to location. This enables presentation of data in map form. Therefore, the application of GIS is possible also in the field of library services, either for analysis of current services or for planning current or future services. By applying GIS, demographical data can be added to geographical data, which can result in better analysis or planning. In the paper the possibility of GIS application in the field of librarianship is presented, especially acquisition and use of publicly accessible geographical and demographical data. The majority of the needed data already exists, one only needs to find and use them properly. When using the already existing data we contribute to cost effectiveness and to the improvement of efficiency.
Keywords: splošne knjižnice; knjižnične storitve; geografski podatki; demografski podatki; knjižnični informacijski sistemi; statistična analiza